An Experimental Study on the Compression of the Fallen Leaf Pellets Using Rollers and Compression Molding Technology - Dang, Thành Trung (Journal of Technical Education Science, 2022)
In order to reduce carbon emissions and sustainably use renewable energy that are less harmful to the environment, biomass energy sources are being encouraged to research and use by the international organizations. This paper presented an experimental investigation on the compression of fallen leaf pellets using rollers and compression molding technology. The adhesive materials were used to experiment with compressing the fallen leaf pellets: rice husks, water, and flour powder. The experimental results show the best performance for the leaf pellet mixed with 20% water (ratio 8-2). At this ratio, the average compression efficiency is up to 98%. Also with this ratio, the average humidity of the pellets is 23.5%. This combustive fuel’s humidity range is capable of supplying the biomass boiler. The capacity of the leaf pellet machine is about 50 kg/h.